The surface treatment influence on the fatigue crack propagation of Al 7050-T7451 alloy - Carvalho, A. L. M.; Voorwald, Herman Jacobus Cornelis [UNESP] (Elsevier B.V. Sa, 2009)
The objective of this research is to evaluate 100 mu m, thickness hard chromium electroplated coating on the fatigue crack propagation of Al 7050-T7451 alloy. The shot peening process was carried out to create residual stresses using ceramic and glass shots. Reverse bending fatigue tests were performed with base material, base material chromium electroplated and base material shot peened and chromium electroplated. In order to study the influence of residual stresses on fatigue life, the compressive residual stress field was measured by an X-ray diffraction method. Scanning electron microscopy technique was used to analyze fracture surface and identify crack origin sites. Glass shot peening results are better with respect to fatigue crack nucleation and propagation in comparison to ceramic shot peening. An overpeening may have occurred which produced damages on the ceramic shot peened surface. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Fatigue; Al 7050-T7451 alloy; Shot peening; Chromium electroplating